What do clinicians think about group parent-led cognitive behaviour therapy for children with anxiety problems in Iceland? - Elísabet Freyja Þorleifsdóttir 2001- (2024)
This study seeks to explore clinicians' views on group parent-led CBT therapy for children with anxiety disorder. Anxiety is the most common mental health disorder amongst children worldwide. It is estimated that by the age of 14, 38% of children will already have met the diagnostics criteria for anxiety disorder, thus children must receive proper, early treatment so that it does not progress into more serious mental disorders. Data was collected through an online survey, where 16 clinicians from different working fields, ages 20-49, answered questions regarding their experiences and views on parent-led CBT. The results show that parents' involvement in their child's treatment is essential. Parent-led CBT group therapy is an effective way to deal with children's anxiety problems. Further research is needed to explore the variation of implementing parent-led CBT in clinical practice and its long-term effectiveness. Keywords: Parent-led CBT therapy, children with anxiety, parents involvement, clinicians thoughts Markmið þessara rannsóknar er að skoða hvað meðferðaraðilum finnst um foreldramiðaða hugræna atferlismeðferð (Foreldra-HAM), í hóp, við kvíðavanda barna. Kvíði er algengasta geðröskun barna í heiminum. Áætlað er að við 14 ára aldur, 38% muni helmingur barna nú þegar hafa uppfyllt greiningarskilyrði fyrir kvíðaröskun, þess vegna er mikilvægt að börn fái viðeigandi meðferð og snemma svo að vandamálið þróist ekki yfir í alvarlegri geðvandamál. Gögnum var safnað með netkönnun þar sem 16 meðferðaraðilar, á mismunandi starfssviðum, á aldrinum 20-49 ára svöruðu reynslu sinni og skoðunum á foreldramiðaða hugræna atferlismeðferð. Niðurstöðurnar sýna að þátttaka foreldra í meðferð barna sinna er nauðsynleg og að foreldra-HAM er áhrifarík leið til að takast á við kvíðavanda barna. Þörf er á frekari rannsóknum svo hægt sé að innleiða foreldra-HAM á víðara sviði og langtíma áhrif þess. Lykilorð: Foreldra-HAM, börn með kvíða, þátttaka foreldra, álit meðferðaraðila